Menyingkap Aspek Penting pada Keputusan Pembelian Konsumen Bimbingan Belajar Persiapan Masuk Universitas Impian (PMUI) Kota Depok - Immanuel, Immanuel; Sihaloho, Noverika; Nuraini, Febri; Cahya Agusti, Dirga; Abdullah, Muhammad (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2024)
This study aims to investigate the influence of brand image and brand awareness on consumer purchasing decisions at the "Persiapan Masuk Universitas Impian" (PMUI) tutoring center in Depok. In the face of increasing competition in the tutoring industry, a deep understanding of how brand image and brand awareness influence consumer purchasing decisions is crucial. The research employed a quantitative approach involving 95 respondents. The study population consisted of all consumers who registered at PMUI Depok between November and December 2023, totaling 125 individuals, with a sample selected using probability sampling, specifically simple random sampling. Data were collected via an online questionnaire distributed through Google Forms and analyzed using multiple regression analysis with SPSS version 25. The results indicated that brand image and brand awareness have a significant impact on consumer purchasing decisions at PMUI Depok. A positive brand image, particularly related to the quality of instructors, enhances consumer confidence. However, diversification of learning programs is necessary to meet the needs of a larger number of consumers. Brand awareness, especially in terms of brand recognition, plays an important role, while brand recall needs to be strengthened through active promotion on social media and collaboration with influencers. Price is also a key consideration in purchasing decisions, so PMUI should offer competitive pricing or discount programs. Loyalty programs and reward schemes can further enhance consumer purchasing decisions. By strengthening brand image, brand awareness, and considering price factors, PMUI can improve its competitiveness and position in the market.